The influence of native wheat lipids on the rheological properties and microstructure of dough and bread - Cropper, Sherrill Lyne (Kansas State University, 2015)
Bread quality and final crumb grain are reflective of the ability for wheat flour dough to retain and stabilize gas cells during the baking process. The visco-elastic properties of dough allow for the incorporation of air cells and expansion during fermentation and baking. The gluten-starch matrix provides the backbone support. However, following the end of proofing and during the beginning of baking, the structure weakens due to over-extension and expansion and the matrix begins to separate and eventually break down. Native wheat lipids, which are found in small quantities in wheat flour, provide a secondary support for gas cell stabilization because of their amphiphilic characteristics and ability to move to the interface and form condensed monolayers. The objectives of this research were to evaluate the influence of native wheat lipids on the rheological properties of dough and the microstructure of bread. Native wheat lipids were extracted from straight-grade flour and separated into total, free, bound, nonpolar, glycolipids, and phospholipids using solid-phase extraction (SPE) with polar and nonpolar solvents. Defatted flour was reconstituted using each lipid fraction at a range of levels between 0.2% and 2.8%. Dough and bread were made following AACC Method 10-10.03. Rheological testing of the dough and evaluation of the microstructure of the bread was conducted using small and large deformation testing, C-Cell imaging, and x-ray microtomography analysis to determine changes in visco-elastic properties and gas cell structure and distribution. Rheological assessment through small amplitude oscillatory measurements demonstrated that nonpolar, phospholipids, and glycolipid fractions had a greater interaction with both proteins and starch in the matrix, creating weaker dough. Nonpolar, phospholipids, and glycolipids, varied in their ability to stabilize gas cells as determined by strain hardening index. C-Cell imaging and x-ray microtomograpy testing found that treatments containing higher concentrations of polar lipids (glycolipids and phospholipids) had a greater effect on overall loaf volume, cell size, and distribution. This illustrates that level and type of native wheat lipids influence the visco-elastic properties of dough and gas cell size, distribution, cell wall thickness, and cell stability in bread.
Keywords: Native wheat lipids; Rheology; X-ray Microtomography; Microstructure; C-Cell Imaging; Food Science (0359)